2009
DOI: 10.1074/jbc.m109.020362
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Membrane Type 1 Matrix Metalloproteinase Cytoplasmic Tail Enhances Tumor Cell Invasion and Proliferation in Three-dimensional Collagen Matrices

Abstract: Increasing evidence suggests that the cytoplasmic tail of membrane type 1 matrix metalloproteinase (MT1-MMP) is subject to phosphorylation and that this modification may influence its enzymatic activity at the cell surface. In this study, phosphorylated MT1-MMP is detected using a phospho-specific antibody recognizing a protein kinase C consensus sequence (phospho-TXR), and a MT1-MMP tail peptide is phosphorylated by exogenous protein kinase C. To characterize the potential role of cytoplasmic residue Thr 567 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
58
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 41 publications
8
58
0
Order By: Relevance
“…Because it has been reported that the S100A8 and S100A9 heterodimerize to yield maximum the stimulation of gene expression, we treated B16F10 cells with a combination of recombinant S100A8 (1 g/ml) and S100A9 (1 g/ml) and determined the mRNA and protein levels of MMP-2, MMP-9, and MMP-14. We chose to study these three MMPs because it has been previously reported that these proteinases confer invasiveness to tumor cells promoting metastasis (42,43). The results of real time RT-PCR revealed that the mRNA levels of MMP-2, MMP-9, and MMP-14 in B16F10 cells treated with a combination of S100A8 and S100A9 were mark-FIGURE 6.…”
Section: Elevated Levels Of Metastasis In the Lungs Of Mice Lacking Umentioning
confidence: 99%
“…Because it has been reported that the S100A8 and S100A9 heterodimerize to yield maximum the stimulation of gene expression, we treated B16F10 cells with a combination of recombinant S100A8 (1 g/ml) and S100A9 (1 g/ml) and determined the mRNA and protein levels of MMP-2, MMP-9, and MMP-14. We chose to study these three MMPs because it has been previously reported that these proteinases confer invasiveness to tumor cells promoting metastasis (42,43). The results of real time RT-PCR revealed that the mRNA levels of MMP-2, MMP-9, and MMP-14 in B16F10 cells treated with a combination of S100A8 and S100A9 were mark-FIGURE 6.…”
Section: Elevated Levels Of Metastasis In the Lungs Of Mice Lacking Umentioning
confidence: 99%
“…Trafficking of MT1-MMP occurs rapidly because cell surface levels of MT1-MMP transiently increase within 20 min of PMA treatment (17,26). Recently, it was shown using an in vitro kinase assay that MT1-MMP is phosphorylated in a PKCdependent manner (27). Here, we tested whether MT1-MMP is phosphorylated in vivo upon PMA treatment and examined the effects of this phosphorylation on MT1-MMP trafficking, cell migration, and cell invasion.…”
Section: Pma Stimulates Mt1-mmp Phosphorylation-phorbolmentioning
confidence: 99%
“…cating that MT1 -MMP functions as a signaling molecule 71,72) . TIMP -2 and MT1 -MMP siRNA enhanced the increased levels of TF antigen and activity, and further reduced the decreased levels of TM antigen in TNF -α -stimulated ECs, indicating that MT1 -MMP may be critical for the modulation of procoagulant states in TNF -α stimulation.…”
Section: Membrane Type 1-matrix Metalloproteinase (Mt1 -Mmp) Identifimentioning
confidence: 99%